Collagen type I enhance cell growth and insulin biosynthesis in rat pancreatic cells. (August 2021) - Zhu, Yingying; Ikejima, Takashi; Liu, Weiwei; Chen, Shuaigao; Xu, Fanxing; Zhang, Luxin; Hayashi, Toshihiko; Mizuno, Kazunori; Hattori, Shunji; Fujisaki, Hitomi; Ikejima, Takashi
Abstract : Type I collagen (collagen I) is the most abundant component of ECM in pancreas. We previously reported that collagen I-coated culture dishes enhanced proliferation of rat pancreatic β cell line, INS-1 cells, via up-regulation of β-catenin nuclear translocation. In this study, we further investigated the effects of collagen I on insulin production of INS-1 cells. The results indicate that insulin synthesis as well as cell proliferation is increased in the INS-1 cells cultured on the dishes coated with collagen I. Up regulation of insulin-like growth factor 1 receptor (IGF-1R) on the INS-1 cells cultured on the collagen-coated dishes is involved in up-regulation of cell proliferation and increase of insulin biosynthesis; however, up-regulation of insulin secretion in the INS-1 cells on collagen I-coated dishes was further enhanced by inhibition of IGF-1R. Autophagy of INS-1 cells on collagen I-coated dishes was repressed via IGF-1R upregulation, and inhibition of autophagy with 3MA further enhanced cell proliferation and insulin biosynthesis, but did not affect insulin secretion. E-cadherin/β-catenin adherent junction complexes are stabilized by autophagy. That is, autophagy negatively regulates nuclear translocation of β-catenin that leads to insulin biosynthesis and cell proliferation. In conclusion, IGF-1R/down regulation of autophagy/nuclear translocation of β-catenin is involved in collagen I-induced INS-1 cell proliferation and insulin synthesis.